(untitled) (The International Journal for Scientific Research, 2022)
The combination of innovation and advancement in healthcare has been a parcel of consideration for a long time. This introductory survey assesses the effect of innovation integration on improving the quality of care. Through a comprehensive writing audit, diverse strategies and discoveries were analyzed to explain the role of innovation in making strides toward well-being. Fundamental findings highlight innovation integration’s numerous benefits, challenges, and openings. The taking-after talking plunges into the suggestions of these discoveries and offers recommendations for future propels in therapeutic innovation. Critically, this audit highlights the significance of utilizing new innovations to progress healthcare and make strides toward patient outcomes.